HPV‐Related Cancers After Solid Organ Transplantation in the United States. Issue 12 (1st October 2013) - Madeleine, M. M.; Finch, J. L.; Lynch, C. F.; Goodman, M. T.; Engels, E. A.
Abstract Transplant recipients have elevated cancer risk including risk of human papillomavirus (HPV)‐associated cancers of the cervix, anus, penis, vagina, vulva and oropharynx. We examined the incidence of HPV‐related cancers in 187 649 US recipients in the Transplant Cancer Match Study. Standardized incidence ratios (SIRs) compared incidence rates to the general population, and incidence rate ratios (IRRs) compared rates across transplant subgroups. We observed elevated incidence of HPV‐related cancers (SIRs: in situ 3.3–20.3, invasive 2.2–7.3), except for invasive cervical cancer (SIR 1.0). Incidence increased with time since transplant for vulvar, anal and penile cancers (IRRs 2.1–4.6 for 5+ vs. <2 years). Immunophenotype, characterized by decreased incidence with HLA DRB1:13 and increased incidence with B:44, contributed to susceptibility at several sites. Use of specific immunosuppressive medications was variably associated with incidence; for example, tacrolimus, was associated with reduced incidence for some anogenital cancers (IRRs 0.4–0.7) but increased incidence of oropharyngeal cancer (IRR 2.1). Thus, specific features associated with recipient characteristics, transplanted organs and medications are associated with incidence of HPV‐related cancers after transplant. The absence of increased incidence of invasive cervical cancer highlights the success of cervical screening in this population and suggests a need for screening for other HPV‐related cancers.